Psychotropic drugs cross-reactivity with amphetamines in a FAERS sample: an international pharmacovigilance study. (1st June 2022) - Giacovelli, L.; Battini, V.; Boscacci, M.; Carnovale, C.; Dell'Osso, B.
Abstract : Introduction: Urine Drug Screening (USD) is one of the most used techniques for drug testing. However, one of the main issues related to USD is the high frequency of cross-reactivity with other molecules. Amphetamines, because of their simple structures, are highly subjected to cross-reactivity with other molecules. Objectives: Our aim was to investigate and characterize the role of psychopharmacological drugs in the occurrence of false-positive amphetamine drug screening, by performing an international pharmacovigilance study through the Food and Drug Administration Adverse Event Reporting System (FAERS), in which user's medication errors for drugs are reported in the form of Individual Case Safety Reports (ICSRs). Methods: All ICSRs recorded between 2010 and 2020 with a positive screening for amphetamine reported as adverse reaction in patients with a psychiatric diagnosis were included in the study. Duplicated records and ICSRs with missing values for age and gender, were excluded from the study. Results: Among 249 ICSRs involving false-positive amphetamine drug screening, 109 ICSRs reported psychiatric disorders and/or psychiatric drugs. In 83 (76%) cases, drugs were known for cross-react. 66 cases reported drugs known as "suspect". 24% of cases reported unknown false-positive reactions: acetaminophen (5%), duloxetine (5%) and oxycodone (5%). Conclusions: The high cross-reactivity of psychotropic drugs with amphetamine testing in USDs may be linked to the neuromodulatory effect of these drugs, suggesting a similar molecular structure. In this perspective, antidepressants and amphetamines share a similar mechanism of action, maybe partially explaining why the most reported cross-reactions are with antidepressant (59%). Disclosure: No significant relationships.